Interview: A 20-year 'search for evidence' leads to the Center for Medical Technology Policy. (January 2014) - Tunis, Sean R
Sean R Tunis is the founder, President and Chief Executive Officer of the Center for Medical Technology Policy in Baltimore (MD, USA). The Center for Medical Technology Policy's main objective is to improve the quality, relevance and efficiency of clinical research by providing a neutral forum for collaboration among experts, stakeholders and decision-makers. Tunis was a member of the Institute of Medicine Committee on Initial National Priorities for Comparative Effectiveness Research. He advises a wide range of domestic and international public and private healthcare organizations on issues of comparative effectiveness, evidence-based medicine, clinical research, reimbursement and health technology policy. In September of 2005, Tunis was the Chief Medical Officer at the Centers for Medicare and Medicaid Services, where he had lead responsibility for clinical policy for the Medicare and Medicaid programs. Previously, he served as the Director of the Health Program at the Congressional Office of Technology Assessment and as a health policy advisor to the US Senate, where he worked on pharmaceutical and device policy issues. Tunis trained at the University of California in Los Angeles (CA, USA) and the University of Maryland in Internal Medicine and Emergency Medicine (MD, USA) and holds adjunct faculty positions at the Tufts University School of Medicine (MA, USA), the Department of Internal Medicine at the Johns Hopkins School of Medicine (MD, USA), and the Department of Surgery at the University of California at San Francisco (CA, USA).